Analysis of Herbaceous Plant Succession and Dispersal Mechanisms in Deglaciated Terrain on Mt. Yulong, China. (23rd October 2014) - Chang, Li; He, Yuanqing; Yang, Taibao; Du, Jiankuo; Niu, Hewen; Pu, Tao
Abstract : Ecological succession itself could be a theoretical reference for ecosystem restoration and reconstruction. Glacier forelands are ideal places for investigating plant succession because there are representative ecological succession records at long temporal scales. Based on field observations and experimental data on the foreland of Baishui number 1 Glacier on Mt. Yulong, the succession and dispersal mechanisms of dominant plant species were examined by using numerical classification and ordination methods. Fifty samples were first classified into nine community types and then into three succession stages. The three succession stages occurred about 9–13, 13–102, and 110–400 years ago, respectively. The earliest succession stage contained the association of Arenaria delavayi + Meconopsis horridula . The middle stage contained the associations of Arenaria delavayi + Kobresia fragilis, Carex capilliformis + Polygonum macrophyllum, Carex kansuensis, and also Pedicularis rupicola . The last stage included the associations of Kobresia fragilis + Carex capilliformis, Kobresia fragilis, Kobresia fragilis + Ligusticum rechingerana, and Kobresia fragilis + Ligusticum sikiangense . The tendency of the succession was from bare land to sparse vegetation and then to alpine meadow. In addition, three modes of dispersal were observed, namely, anemochory, mammalichory, and myrmecochory. The dispersal modes of dominant species in plant succession process were evolved from anemochory to zoochory.